Is cohesive capitalism under threat?. (8th November 2021) - Besley, Timothy
Abstract: This paper argues that a distinctive form of capitalism, cohesive capitalism, emerged in the post-war period supporting the wellbeing of its citizens through building state capacities alongside open and democratic forms of government. The paper identifies a range of threats that this model now faces and speculates on what it would take, particularly in terms of international cooperation, to respond to them.